A Comparison of the Clinical Performance Between the Lateral Sinus Lifts and Percrestal Sinus Lifts in Severely Atrophied Posterior Maxilla - AlBattrawi, Salma; Doghramje, Tania; Tippu, Mohammed Shoaib ur Rahman; Azim, Sabrin Ali; Moharamzadeh, Keyvan (International Journal of Membrane Science and Technology, 2023)
Aim/Objective: The objective of our study is to compare the clinical performance between the lateral sinus lift and the percrestal sinus lift techniques in severely atrophied posterior maxilla.Materials and Methods: An electronic search was done by three independent reviewers using a computerized search involving multiple databases focusing on comparative articles discussing the differences between lateral sinus lift technique and percrestal sinus lift technique. The search involved a solid application of the authors’ inclusion and exclusion criteria. Results: The combined search done by the authors identified 19 eligible articles. 13 of which were excluded strictly based on the inclusion and the exclusion criteria leaving us with 6 accepted articles to conduct this systemic review. 3 of the articles are clinical trials, 2 are retrospective studies and 1 is a prospective study. In all of the 6 selected articles, a comparative discussion between the lateral sinus lift technique and percrestal sinus lift technique was done. Conclusions: The lateral sinus lift technique has higher morbidity and success rates when compared to the percrestal sinus lift technique. However, that does not eliminate the fact that the latter is still a viable choice if a less invasive is necessary or if the alveolar height at baseline is not as diminished.